2017
DOI: 10.4236/ajmb.2017.71006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplemental Oregano Essential Oils in Diets on Production Performance and Relatively Intestinal Parameters of Laying Hens

Abstract: This study was designed to investigate the effects of dietary oregano essential oils on 150 30-week-old Hy-Line Layers' productive performance, egg quality characteristics, cecal microbiota, digestive enzyme activities, mucosa structure of the duodenum and jejunum and glucose and small peptides transporters expression in the duodenum and jejunum. All hens were allocated into one of five different groups: negative control (NC; basal diet only), antibiotics control (CS; basal diet plus 100 mg/kg of 10% colistin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 22 publications
(21 reference statements)
7
25
1
Order By: Relevance
“…The expression level of GLUT2 was also up‐regulated in the jejunum and ileum mucosa. The results obtained in this study were consistent with previous report that both the SGLT1 and GLUT2 genes in the intestinal mucosa were significantly up‐regulated by oregano essential oils in laying hens (He et al, ). These results provided a molecular basis for improved nutrient absorption after dietary PEO supplementation.…”
Section: Discussionsupporting
confidence: 93%
“…The expression level of GLUT2 was also up‐regulated in the jejunum and ileum mucosa. The results obtained in this study were consistent with previous report that both the SGLT1 and GLUT2 genes in the intestinal mucosa were significantly up‐regulated by oregano essential oils in laying hens (He et al, ). These results provided a molecular basis for improved nutrient absorption after dietary PEO supplementation.…”
Section: Discussionsupporting
confidence: 93%
“…The same later author reported that the use of 1.0% oregano in the diet was increased egg production and egg weight of hens. He et al (2017) indicated that oregano essential oil enhanced average egg weight and feed efficiency on laying hens. These results the oregano essential oils may enhance the intestinal health and digestibility of the feeds and thus improve the performance of laying hens (He et al, 2017).…”
Section: Productive Performancementioning
confidence: 99%
“…These results are in agreement with those reported by Oussalah et al (2006), who studied 3 oregano varieties: the first (Origanum heracleoticum) from France, rich in carvacrol (54%); the second (Origanum compactum) from Morocco, rich both in carvacrol (22%) and γ-terpinene (23%); and the third (Origanum majorana) from Egypt, rich in terpinene-4-ol (26%) and γterpinene (12%). Mathlouthi et al (2012) and He et al (2017) found that the essential oil isolated from oregano was characterized by its increased content of carvacrol (69.55%) and (73.06), respectively.…”
Section: Chemical Composition Of Rosemary and Oregano Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the pharmacologically active principle, the essential oils consist of mixtures of volatile substances, usually lipophilic, whose components include terpene hydrocarbons, simple alcohols, aldehydes, ketones, phenols, esters, organic acids, etc [3] A research [4] evaluating layers fed with colistin rations (100mg/ kg), and doses of oregano essential oil (50, 100 and 150mg / kg of ration), observed a better egg laying rate and egg weight with 100mg/kg of oregano essential oil. Likewise, this treatment promoted a better mass conversion of eggs, with no losses in egg quality, considering Haugh units.…”
Section: Essential Oilsmentioning
confidence: 99%